Peluang Dan Ancaman Perdagangan Bebas Negara Asean Komoditi Pertanian : Studi Kasus Indonesia Dan Kamboja - Daspar; Martiana Putri Rahayu; Serli Agustin Rahayu; Nurhanifah Zainum Mutttaqin; Mela Reza (CV. ITTC INDONESIA, 2024)
Free trade opens up new opportunities for the Indonesian and Cambodian agricultural sectors. With the reduction of tariffs and trade barriers, market access for agricultural products in both countries is increasingly open. Indonesia has the opportunity to increase exports of commodities such as palm oil, coffee, tea and other plantation products to Cambodia. Meanwhile, Cambodia has the opportunity to export rice, vegetables and tropical fruit to Indonesia. This can encourage the growth of agricultural production and increase farmer incomes in both countries. However, free trade also poses the threat of intense competition. Imported agricultural products can flood the domestic market and displace local products if they are less competitive. Small-scale farmers in both countries have the potential to be marginalized if they cannot adopt efficient agricultural technologies and practices. In addition, strict quality and food safety standards can limit export access if they are not met properly. To optimize opportunities and mitigate threats, steps are needed such as increasing the productivity and competitiveness of superior commodities, strengthening the capacity of farmers and agricultural entrepreneurs, as well as harmonizing quality standards and certification. Technical cooperation, technology transfer and trade facilitation between the two countries are also the keys to achieving maximum benefits from free trade in agricultural commodities.